Impact of maternal diabetes on birthweight is greater in non-Hispanic blacks than in non-Hispanic whites - Hunt, Kelly J. (2012)
AIMS/HYPOTHESIS: To determine the impact of maternal diabetes during pregnancy on racial disparities in fetal growth. METHODS: Using linked birth certificate, inpatient hospital and prenatal claims data we examined live singleton births of South Carolina resident mothers, who self-reported their race as non-Hispanic white (NHW, 140128) or non-Hispanic black (NHB, 82492) and delivered at 28 to 42 weeks gestational age 2004 through 2008. RESULTS: Pre-pregnancy diabetes prevalence was higher in NHB (3.0%) than NHW (1.7%), while gestational diabetes (GDM) prevalence was similar in NHB (6.1%) and NHW (6.3%). At a delivery BMI of 35 kg/m(2), GDM exposure was associated with an average birthweight only 17 grams (95% CI: 4, 30) higher in NHW, but 78 grams (95% CI: 61, 95) higher in NHBs (controlling for gestational age, maternal age, infant sex, and having information on prenatal care). Numbers for pre-pregnancy diabetes were 58 grams (95% CI: 34, 81) in NHWs and 60 grams (95% CI: 37, 84) in NHBs. GDM had a greater impact on birthweight in NHBs than on NHWs [60 gram racial difference (95 % CI: 39, 82)], while pre-pregnancy diabetes had a large but similar impact. Similarly, the risk ratio for GDM of having a large relative to a normal weight for gestational age infant was lower in NHW [RR=1.41 (95% CI: 1.34, 1.49)] than in NHB [RR= 2.24 (95% CI: 2.05, 2.46)] women. CONCLUSIONS/INTERPRETATION: These data suggest that the negative effects of GDM combined with obesity during pregnancy may be greater in NHB than NHW individuals.